Long-term dentoskeletal and profile changes after orthodontic treatment with and without teeth extractions - Peloso, Renan Morais (2024)
Introduction: This study aimed to evaluate the impact of long-term orthodontic treatment with and without teeth extractions in soft tissue and dentoskeletal variables. Methods: The sample was comprised of cephalometric radiographs of forty patients orthodontically treated with and without premolar extractions. The patients were evaluated in pretreatment (T1); posttreatment (T2) and long-term follow-up (T3) times. Two groups were formed according to the protocol treatment. The Extraction Group: 24 patients (16 female, 8 male), with mean ages of 13.14 (T1), 15.50 (T2), and 52.49 years (T3). Mean treatment time (T2-T1) and long-term follow-up (T3-T2) of 2.36 and 36.99 years, respectively. The Nonextraction Group: 16 patients (10 female, 6 male), with mean ages of 15.18 (T1), 17.03 (T2), and 53.61 years (T3). Mean treatment time (T2-T1) and long-term follow-up (T3-T2) of 1.85 and 36.58 years, respectively. The cephalometric analysis of soft tissue and dentoskeletal was performed using Dolphin Imaging Software. The independent t test was used for intergroup comparisons. Results: The nonextraction group had a short treatment time (p=0.31). The extraction group showed significant mandibular incisor retraction during the treatment (p=0.019). Both groups presented similar changes in soft tissue and dentoskeletal variables after long-term follow-up. Conclusions: The orthodontic treatment with and without extractions presented similar changes in soft tissue and dentoskeletal variables after a 37-year follow-up.